Biocompatibility of low molecular weight polymers for two‐phase partitioning bioreactors. Issue 12 (14th July 2015) - Harris, Jesse; Daugulis, Andrew J.
ABSTRACT: Two phase partitioning bioreactors (TPPBs) improve the efficiency of fermentative processes by limiting the exposure of microorganisms to toxic solutes by sequestering them into a non‐aqueous phase (NAP). A potential limitation of this technology, when using immiscible organic solvents as the NAP, is the cytoxicity that these materials may exert on the microbes. An improved TPPB configuration is one in which polymeric NAPs are used to replace organic solvents in order to take advantage of their low cost, improved handling qualities, and biocompatibility. A recent study has shown that low molecular weight polymers may confer improved solute uptake relative to high molecular weight polymers (i.e., have higher partition coefficients), but it is unknown whether sufficiently low molecular weight polymers may inhibit cell growth. This study has investigated the biocompatibility of a range of low molecular weight polymers, and compared trends in biocompatibility to the well‐established "critical log P" concept. This was achieved by determining the biocompatibility of polypropylene glycol polymers over a molecular weight (MW) range of 425–4, 000 to Saccharomyces cerevisiae and Pseudomonas putida, two organisms which have been previously used in TPPB systems. The lower MW polymers were shown to have lower average log P values, and showed more cytotoxicity than polymers of the same structure but with higher molecular weight. Since polymers are generally polydisperse (i.e., polymer samples contain a distribution of MWs), removal of the lower MW fractions via water washing was found to result in improved polymer biocompatibility. These results suggest that the critical log P concept remains useful for describing the toxicity of polymeric substances of different MWs, although it is complicated by the presence of the low MW fractions in the polymers arising from polydispersity. Biotechnol. Bioeng. 2015;112: 2450–2458. © 2015 Wiley Periodicals, Inc. Abstract : Twenty four hours cultures of Pseudomonades putida . Vials show control conditions, and 20% w/v exposure to polypropylene glycol with the molecular weight of 425, 4, 000, and washed 425. The washed PPG was mixed with an equal volume of water for 2 min to remove the most water soluble fraction from the polymer sample, improving biocompatibility. These results show improved biocompatibility with increasing molecular weight and log P (also known as log KOW ).